Critical Analysis of Nursing Roles in An Evolving Healthcare Landscape - Alshammari, Ayed Radhi Nazzal; Alshammari, Khlood Hussain Hezab; alshammari, fahad hamoud mohammad; alshammari, Abdulrahman dahimish; Alshammary, Ffaisal Radhi Nazal; Alshammari, Awad Hamoud Dhahawi; Alshammari, Hazzaa Matar; Alshammari, Manal Binyah; Alshammari, Abeer Binyah Thayid; Alshammari, Ohud Binyah Thayid (Journal of Ecohumanism, 2024)
The status of nurses working in healthcare facilities has transformed in terms of the relevance of their work to emerging healthcare systems. Taken within the context of a transforming healthcare system, this paper aims to critically discuss the shifts in nursing roles. Challenges like technology, chronic diseases, policy changes, and patient-focused care greatly influence nursing practice today. This paper aims to discuss the effects of the changes on the nursing profession and the competencies that define practice. The paper compares the current literature on this topic and identifies areas that require further training and support for nurses due to emergent demands. Furthermore, the paper provides guidelines on how to improve nurses' roles in healthcare delivery systems to guarantee their proper contribution to the delivery of care and the improvement of patient's health.